School Integration of Autistic Children - Bouteraa, Ibtissem (المدرسة العليا للأساتذة بوزريعة - مخبر تعليم - تكوين - تعليمية, 2020)
We consider that autistic children are ignored in the Algerian society. There is even a lack of statistical data on autistic children in Algeria. In this article, we highlight the importance of integrating the education of children with autism into the school community. We first present the characteristics of autistic children, then discuss the importance of integrating these children into the general education system and subsequently, we present a model that can be used to promote the school integration of these children.
Keywords: التربية الخاصة -- الدمج المدرسي -- أطفال التوحد -- الجزائر